Main diseases related to asbestos exposure: a narrative literature review (Research, Society and Development, 2022)
Introduction: Asbestos (or asbestos) is a ubiquitous and natural fiber that has been linked to the development of malignant and fibrotic diseases of the lung and pleura. These diseases can be initiated by injury to epithelial cells and mesothelial cells by asbestos fibers through the formation of reactive oxygen intermediates. Objective: to characterize the main diseases resulting from asbestos exposure. Methodology: the research was carried out through online access to the National Library of Medicine (PubMed MEDLINE), Scientific Electronic Library Online (Scielo), Cochrane Database of Systematic Reviews (CDSR), Google Scholar, Virtual Health Library (BVS) databases. and EBSCO Information Services, February 2022. Results and Discussion: Inhalation of asbestos fibers can lead to a number of respiratory diseases, including lung cancer, asbestosis, pleural plaques, benign pleural effusion, and malignant mesothelioma. Although exposure is now regulated, patients continue to experience these diseases due to the long latent period between exposure and clinical illness. The signs and symptoms presented tend to be nonspecific; thus, the occupational history helps to guide the clinical suspicion. High-risk populations include people in construction businesses, boilermakers, shipyard workers, railroad workers, and US Navy veterans. Every effort should be made to minimize continued exposure. Final considerations: the appearance of symptoms such as dyspnea, cough, chest discomfort or weight loss requires an immediate and complete evaluation. Therefore, current recommendations support lifelong surveillance for people with a history of significant exposure or ongoing exposure, and knowing the diseases arising from this causality can help the scientific community to help with public health measures.